The moon - Prinja, Raman, 1961- (Chicago, Ill. : Heinemann Library, 2008)
Discover what the surface of the Moon is like and read about the people who have visited the Moon.
What is the moon? -- Does the moon move? -- Why does the moon seem to change shape? -- What is an eclipse of the moon? -- What is the surface of the moon like? -- What is the moon made of? -- What is special about the moon? -- Has anyone visited the moon? -- Could I ever live on the moon? -- Fact file -- Glossary.
Includes bibliographical references (p. 31) and index.
Keywords: Moon -- Juvenile literature; Moon